Eotaxin-1 Levels in Patients with Myocardial Infarction - Kalayci, Mehmet; Gul, Evrim (Clin Lab Publ, 2022)
Background: Acute myocardial infarction is one of the leading causes of morbidity and mortality worldwide. Eo-taxin-1, an eosinophil-specific chemoattractant, has been shown to be overexpressed in human atherosclerotic le-sions. Eotaxin-1 levels are higher in coronary artery disease patients than in healthy individuals. In this study, we aimed to determine the eotaxin-1 concentrations of patients with myocardial infarction and to investigate the role of eotaxin-1 in myocardial infarction. Methods: The study included 42 patients diagnosed with AMI (patients with suspected AMI based on history, physical examination, ECG, and biochemical markers and confirmed by angiography) and 40 healthy controls. Plasma eotaxin-1 levels were determined by enzyme-linked immunosorbent assay (ELISA). Results: Eotaxin-1, troponin-I, CK, and CKMB levels were statistically higher in the patient group than in the control group. ROC analysis demonstrated that eotaxin-1 gave a sensitivity of 93% and a specificity of 48% once the cutoff value was 341.6 pg/mL. Additionally, the ROC analysis showed that troponin I yielded a specificity of 100% and a sensitivity of 91% when the cutoff value was 0.025 mu g/L. Conclusions: Eotaxin-1/eosinophils appear to have a role in coronary artery disease independent of known risk factors. Accordingly, this study and recent studies suggest that eotaxin-1 may be useful in the diagnosis of AMI in addition to other cardiac markers. (Clin. Lab. 2022;68:xx-xx. DOI: 10.7754/Clin.Lab.2021.210806)
Keywords: eotaxin-1; myocardial infarction; coronary artery disease